Smart Healthcare: Leveraging AI and Cloud Technologies for Enhanced Medical Solutions - Singh, Prabhishek; Diwakar, Manoj; Kumar Pandey, Neeraj; Kumar Mishra, Amit; Gupta, Indrajeet (Bentham Science Publishers, 2026)
Smart Healthcare: Leveraging AI and Cloud Technologies for Enhanced Medical Solutions explores the rapidly evolving convergence of artificial intelligence and cloud computing in modern healthcare systems. This volume brings together cutting-edge research and practical insights that demonstrate how AI and cloud-enabled solutions are improving diagnostics, treatment planning, patient monitoring, data management, and operational efficiency, providing a balanced perspective on both technological innovation and real-world healthcare needs. The chapters present an integrated view of AI techniques such as machine learning and computer vision alongside cloud-based infrastructures that enable scalable, secure, and efficient healthcare delivery. Through real-world case studies and applied examples, the book illustrates measurable improvements in clinical decision-making and healthcare workflows. It also critically examines key challenges, including data privacy, security, interoperability, and regulatory compliance, while proposing practical strategies to address them. Looking ahead, the book discusses emerging trends such as edge computing, blockchain, and intelligent robotics and their potential to further advance smart healthcare ecosystems. Key Features: Examines AI- and cloud-driven innovations in healthcare delivery Demonstrates real-world applications through case studies and examples Addresses data security, privacy, and regulatory challenges Explores emerging technologies shaping the future of smart healthcare